2016
DOI: 10.21037/tlcr.2016.11.01
|View full text |Cite
|
Sign up to set email alerts
|

State of the art of chemotherapy for the treatment of central nervous system metastases from non-small cell lung cancer

Abstract: Chemotherapy is the mainstay of treatment of advanced non-small cell lung cancer (NSCLC) without molecular drivers. Despite a low penetration of central nervous system (CNS), chemotherapy drugs demonstrated encouraging activity against CNS metastases from NSCLC. Based on the available data, chemotherapy should be considered as an important part of the multidisciplinary treatment of CNS metastases. Particularly, platinum-based regimens represent the most active combinations and pemetrexed is associated with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 86 publications
0
9
0
1
Order By: Relevance
“…Platinum‐based chemotherapy is currently considered the first‐line treatment regimen for advanced NSCLC patients . Efficacy and long‐term survival rates in patients treated with a combined chemotherapy regimen are greater than in those administered a non‐platinum chemotherapy regimen; however, the difference according to previously published prospective randomized clinical trials and high quality meta‐analysis was not statistically significant …”
Section: Discussionmentioning
confidence: 97%
“…Platinum‐based chemotherapy is currently considered the first‐line treatment regimen for advanced NSCLC patients . Efficacy and long‐term survival rates in patients treated with a combined chemotherapy regimen are greater than in those administered a non‐platinum chemotherapy regimen; however, the difference according to previously published prospective randomized clinical trials and high quality meta‐analysis was not statistically significant …”
Section: Discussionmentioning
confidence: 97%
“…Despite the fact that patient OVA_378 also demonstrates linear progression, all sampled regions were treatment naive, where the primary and synchronous metastatic tumours continued to clonally expand in parallel converging on driver gene FLNA in late clonal expansions irrespective of therapeutic pressures. Since previous studies have shown carboplatin treatment having limited blood-brain barrier (BBB) penetration (2.6%) and subsequently minimal therapeutic effect in brain metastases, despite its ability to penetrate abnormal BBB, 27 the evolutionary processes in the brain metastasis (OVA_048) were less likely to be affected or shaped by the carboplatin treatment, with all metastatic clones reaching near 100% CCFs. Interestingly, one patient (OVA_003) acquired all somatic mutations in the metastatic tumour from the primary tumour, with no further clonal expansion, even after 20 months, post therapy.…”
Section: Analysis Of Pathways Associated With the Hgsoc Metastatic Prmentioning
confidence: 99%
“…In clinical trials for CNS metastases from lung cancer, cisplatin-paclitaxel and carboplatin-paclitaxel regimens have both demonstrated intracranial RRs comparable to systemic RRs, despite limited CNS penetrance [36][37][38]. This suggests a meaningful role for platinum-based chemotherapy in the treatment of MMMT.…”
Section: Chemotherapy and Targeted Therapymentioning
confidence: 99%